The African Animal Breeding Network as a pathway towards genetic improvement of livestock - Djikeng, Appolinaire; Olori, V.E.; Houaga, I.; Aggrey, S.E.; Okeyo Mwai, Ally; Ibeagha-Awemu, E.M.; Mrode, Raphael A.; Chagunda, M.G.G.; Tiambo, Christian K.; Rekaya, R.; Nash, O.; Nziku, Z.; et al. (2025)
Transforming Africa’s agricultural production and food systems is an imperative to achieve the United Nations Sustainable Development Goals and deliver on the Africa Union’s 2063 vision, the Africa we want’. Transforming livestock systems through genetic improvement will sustainably increase productivity and proffer an inclusive socioeconomic development of farming communities. The African Animal Breeding Network (AABNet) is a platform of highly knowledgeable geneticists, animal breeders and professionals willing to provide information, training, advice and support across the continent. It will leverage available human resources among its members, facilitate partnerships and investment and develop infrastructure for innovative livestock genetic improvement in Africa.